De anônimos a heróis: discursos sobre o câncer de 1973 a 2013 no gênero reportagem de popularização da ciência na revista VEJA - Silva, Veronice Mastella da (2015)
This dissertation is attached to the CNPQ Project Nº 301793/2010-7, Análise crítica de gêneros discursivos em práticas sociais de popularização da ciência (MOTTA-ROTH, 2010), and is developed based in the theoretical and methodological apparatus of Critical Genre Analysis (CGA) that, from assumptions as the dialogism and the polyphony (BAKHTIN, 2011), provides the means to analyze the interaction process between texts and discourses and by the observation of the straight relation between context and text (MOTTA-ROTH, 2006, p. 147). The CGA has interdisciplinary character and is constituted by the confluence between: Systemic Functional Linguistics, more precisely the Systemic Functional Grammar from Halliday (1994) and Halliday and Matthiessen (2004); Socio-Rethoric Studies, mainly in Miller (2009a; 2009b), Swales (1990, 2004), Askehave and Swales (2009) and Bazerman (2011); and Critical Discourse Analysis, especially the postulates from Fairclough (2003, 2008). This is a qualitative and quantitative research, with ethnographic inspiration, whose steps of analysis sometimes present emphasis on social practice and sometimes on discursive practice. We analyzed diachronically (1973-2013) the cancer s representation in the genre of science popularization (SP) reportage in the magazine VEJA. By analyzing 25 selected reportages under the criterion "with cover story , we concentrated in possible angulation changes of the theme cancer (the disease, the scientific advances, the patients), the mobilized voices in the process of scientific discourse recontextualization and the rhetorical procedures in the process of cancer s explanation (and, therefore, representation). The results showed that, through four decades, the discourse of recontextualization changed its approach angle. In the 1970s, the disease was featured. In the 1980s, 1990s and 2000s, the emphasis was given to scientific advances, and, in the 2010s, to the patients. In this discourse, the predominant voices are from the technicians/specialists, which apply the researchers knowledge. This shows that in a neither non-targeted nor specialized magazine as VEJA the trend is that such voices are those receiving more space to explain cancer to non-experts. In this SP process, the most used discursive procedures are the metaphors, especially those from the war field. The results yet showed that the representation in the disease s perspective has not changed. Representations such as war enemy , condemnation , and opponent are reaffirmed over 40 years. However, the patient s representation was altered. From anonymous, undefended , and condemned , they turn to the condition of heroes . In the midst of the SP in the media context, it was possible to verify that are at least three phenomena in the discourse(s): spectacularization , conversalization , and commodification .